Geopolímero mesoporoso obtido a partir de metacaulim e cinza de casca de arroz como alternativa de adsorvente para remoção de corantes - Barbosa, Tuany Ramos (2017)
The industrial activity has contributed greatly to a significant increase in the concentrations of dyes in water, representing an important source of contamination of the water bodies, especially when we consider that such ions can be disseminated through the food chain. Due to these environmental implications, new processes of removal and / or degradation of these compounds in textile effluents have been tested, among them the adsorption. The adsorption process is a potentially versatile, affordable and economical alternative for the treatment of various types of effluents, including those of the textile industries. The objective of this work was a synthesis, characterization of a new geopolymer and the evaluation of the removal capacity of the methyl violet dye 10B. The geopolymer was synthesized from metacaulim, being a clay mineral used in several industrial sectors and, due to the high availability in the earth's crust, chemical modifications were made to obtain different structures of the material, seeking to extend its use, together with the rice husk , With (MGP) and without soybean oil (GP) as the modeling agent. GP, MGP and the precursors were characterized and used to remove methyl violet dye 10B (MV10B) from aqueous solutions. The samples were characterized by X-ray diffractometry (XRD), Spectroscopy in the Infrared Region with Fourier Transform (FTIR). MGP showed much higher characteristics and adsorption potential in relation to GP and precursors. Adsorption studies have shown that MGP is an efficient adsorbent. The equilibrium was reached within 120 min and the maximum adsorption capacity was 276.9 mg / g. MGP is a new alternative adsorber that presented higher porosity, having better results with the methyl violet dye 10B, representing advantages as high efficiency, fast kinetics and high adsorption capacity.